Students' selection of the English Language Courses at Hebron University / Mahmood K. M. Eshreteh, Mohammed A. A. Farrah and Blansh Zaitoon - Mahmood K., M. Eshreteh; Mohammed A., A. Farrah; Blansh, Zaitoon (Universiti Teknologi MARA Cawangan Kedah, 2017)
Decision-making process is one of the most difficult steps during academic life. Sometimes, students find it difficult to decide on choosing the appropriate course. This paper investigates the different factors that students take into account when selecting certain language courses during the academic terms. These factors may include instructor's subject matter and pedagogical knowledge, instructor's personal traits, timing of the course, nature of the course, student personal interests and recommendations from academic advisors, peers, friends, and parents. To assess this issue a questionnaire was distributed to 150 English-major students at Hebron University to explore students’ main considerable factors for their course selection decisions. The results showed that the most considerable factors are timing, the instructor as well as course type, respectively. This study revealed a lot about students reasoning when it comes to choosing a certain course. It will also benefit teachers and decision-makers at the Department of English at Hebron University and other Palestinian institutions of higher learning to understand students’ views and to make some changes accordingly